2022
DOI: 10.1200/jco.2022.40.4_suppl.379
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3 randomized, open-label, multicenter study of tremelimumab (T) and durvalumab (D) as first-line therapy in patients (pts) with unresectable hepatocellular carcinoma (uHCC): HIMALAYA.

Abstract: 379 Background: A single priming dose of T (anti-CTLA-4) added to D (anti-PD-L1) in the STRIDE (Single T Regular Interval D) regimen, formerly T300+D, showed encouraging clinical activity and limited toxicity in a phase 2 uHCC study (Study 22, NCT02519348), suggesting single exposure to T is sufficient to improve upon D activity. HIMALAYA (NCT03298451) evaluated the efficacy and safety of STRIDE or D vs sorafenib (S) in uHCC. Methods: HIMALAYA is an open-label, multicenter, phase 3 study, in which pts with uH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
328
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(334 citation statements)
references
References 0 publications
4
328
0
2
Order By: Relevance
“…The results of this study were recently reported at ASCO Gastrointestinal Cancers Syposium. 42 The combination therapy improved survival compared with sorafenib (16.4 months versus 13.8 months, HR = 0.78, 95% CI 0.65–0.92, p = 0.0035). Single-agent durvalumab was found to be noninferior to sorafenib (HR = 0.86; 95% CI 0.73–1.03).…”
Section: Emerging Systemic Therapeutic Options On the Horizonmentioning
confidence: 94%
“…The results of this study were recently reported at ASCO Gastrointestinal Cancers Syposium. 42 The combination therapy improved survival compared with sorafenib (16.4 months versus 13.8 months, HR = 0.78, 95% CI 0.65–0.92, p = 0.0035). Single-agent durvalumab was found to be noninferior to sorafenib (HR = 0.86; 95% CI 0.73–1.03).…”
Section: Emerging Systemic Therapeutic Options On the Horizonmentioning
confidence: 94%
“… 219 The latest findings of the multicenter, phase III HIMALAYA study based on this revealed the superiority of the higher tremelimumab dose regimen over sorafenib on survival benefits (OS, 16.4 vs 13.8 months, P = 0.0035), thus strongly supporting the use of the Single Tremelimumab Regular Interval Durvalumab regimen (tremelimumab 300 mg+durvalumab 1500 mg followed by durvalumab every 4 weeks) as first-line therapy for aHCC. 220 Moreover, numerous ICI combination regimes ( Table 1 ), like IBI310 (anti-CTLA-4 antibody) plus sintilimab, are undergoing to explore a highly efficacious systemic therapy with a favorable safety profile.…”
Section: Treatment Advances In Systemic Therapymentioning
confidence: 99%
“…Additionally, single agent durvalumab was noninferior to sorafenib, with a median OS of 16.6 versus 13.8 months (HR 0.86, noninferiority margin 1.08) and ORR of 17%. Based on these results, dual ICI combination and single agent durvalumab may become potential first-line systemic therapy options for advanced HCC in the near future ( 61 , 77 ). Other potential targets of checkpoint blockade include TIM-3 and LAG-3, which are both expressed along with PD-1 on CD8+ T cells and contribute to T cell dysfunction and suppression ( 78 ).…”
Section: Future Optionsmentioning
confidence: 99%